1999
DOI: 10.1002/(sici)1521-1878(199812)20:12<992::aid-bies5>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Viral ion channels: molecular modeling and simulation

Abstract: In a number of membrane-bound viruses, ion channels are formed by integral membrane proteins. These channel proteins include M2 from influenza A, NB from influenza B, and, possibly, Vpu from HIV-1. M2 is important in facilitating uncoating of the influenza A viral genome and is the target of amantadine, an anti-influenza drug. The biological roles of NB and Vpu are less certain. In all cases, the protein contains a single transmembrane ␣-helix close to its N-terminus. Channels can be formed by homo-oligomeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…This choice leaves the S residue facing toward the lipid bilayer. This setup is in agreement with experimental measurements by Arkin and co-workers, but differs from the choice made by Sansom et al, (Kukol and Arkin, 1999;Sansom et al, 1998). Once the peptide bundle was inserted into the bilayer, as shown in Fig.…”
Section: Initial Conditionssupporting
confidence: 90%
See 1 more Smart Citation
“…This choice leaves the S residue facing toward the lipid bilayer. This setup is in agreement with experimental measurements by Arkin and co-workers, but differs from the choice made by Sansom et al, (Kukol and Arkin, 1999;Sansom et al, 1998). Once the peptide bundle was inserted into the bilayer, as shown in Fig.…”
Section: Initial Conditionssupporting
confidence: 90%
“…The orientation of these domains has been confirmed for VPU and other ion channels by using NMR to probe the tilt angle (Zheng et al, 2001;Marassi and Opella, 2000). Computational approaches to the elucidation of the structure of TM proteins have also shown that small proteins topologically similar to VPU will align more or less perpendicular to the bilayer surface (Sansom et al, 1998).…”
Section: Introductionmentioning
confidence: 91%
“…The M2 channel protein from influenza A virus ( Fig. 1) provides a good test case for modeling studies of simple membrane proteins (34,35). It is a 97-residue protein containing a single TM a-helix.…”
Section: Introductionmentioning
confidence: 99%
“…A relatively simple class of ion channels is provided by a number of virally encoded membrane proteins 7, 8. These may provide a paradigm for ion channel folding and assembly.…”
Section: Introductionmentioning
confidence: 99%